Crashworthiness performance of the designed concave hexagonal structures as filler element in cylindrical shells in multiple load cases - Andre Hartawan Mettanadi; Aditya Rio Prabowo; Bambang Kusharjanta; Fajar Budi Laksono; Haris Nubli (Fracture and Structural Integrity)
Safety Impact resistance is defined as the ability of a material to absorb impact energy through a controlled failure mechanism. The greater the energy absorption by the crash safety structure, the greater the safety in preventing deformation of the main structure due to impact. Based on the data provided by Statista, in 2020 there were 2,395 people died in road accidents in Italy, that number is still high, so we need vehicle components that are able to protect us from the effects of collisions so that the passengers can be protected. In this study, numerical validation, mesh convergence studies, and multiple load case studies were performed to investigate crash resistance of crashworthiness structure under axial loading. Numerical validation results showed that the similarity between this study and the reference reaches 95%. A deviation of 5% occurred due to different input material properties. The results showed that the concave hexagons as filling elements had greater energy absorption capacity than conventional hollow tubes, and the more concave hexagonal structures, the better the energy absorption. Oblique compression was performed in this study, and as a result, the sample had good impact resistance at low angles and no effect at high angles like 20. Therefore, this research aims to improve multi-cell structures for the energy absorption